I wouldn’t mind moving actually: exploring student mobility in Northern Ireland - Cairns, D. (2015)
This article examines orientations towards future geographical mobility amongst young people in Northern Ireland presently studying at third level educational institutions. Following contextualisation of youth mobility as pertaining to students in this region, the results of recent quantitative and qualitative research are discussed. Over half of these young people, 55 per cent, see themselves living outside Northern Ireland at some point in the future. Furthermore, in response to a number of statements on family relationships, peer associations and community attachments, young people with mobility intentions are found to be more likely to have families who support migration intentions. These potentially mobile young people also tend to have peers and siblings with prior experience of geographical mobility and show signs of being less deeply attached to their local communities and/or local identities. A number of qualitative case studies further illustrate the diversity of mobility orientations within the sample, ranging from those positively predisposed towards migration to those more averse to such movement.